Obiektywistyczna teoria prawa własności intelektualnej i jej krytyka: [The objectivist theory of intellectual property and its critique] (Studia Prawnicze / The Legal Studies, 2016)
Nie ulega wątpliwości, że jednym z najczytelniejszych kryteriów podziału nurtów myśli libertariańskiej czy też doktryn polityczno-prawnych w ogóle jest stosunek do prawa własności. Wszystkich przedstawicieli libertarianizmu łączy bowiem przekonanie o naczelnej pozycji wolności jednostki, lecz – podobnie jak to ma miejsce w liberalizmie – autonomia jednostki może być powiązana z pra-wem własności prywatnej (wówczas do czynienia mamy z tzw. libertarianizmem prawicowym) albo z prawem do udziału w powszechnie dostępnych dobrach na-tury (przekonanie charakterystyczne dla odłamu lewicowego). Among many libertarian theories of property, the objectivist “creationist” is one of the most interesting – especially when applied to the problem of intellectual property. First, it is deontological and rules out fiduciary titles to ideal goods based on the positive law. Second, it legitimizes both patents and copyright and regards these institutions as kinds of property. This of course poses a challenge for a system that claims that a right to (acquire) property is absolute. Third, Ayn Rand’s philosophy cherishes great minds of entrepreneurs, inventors and artists, thus making its stance on IP even more significant. Set in Lockean desert-justice, labor theory of property, objectivism claims that an act of projection of a labor onto the nature comprises both physical and mental aspects. A thing to be appropriated needs to be recognized as “a good” first (and thus it is created; moreover, ideal goods are created ex nihilo). Although, the creationist theory cannot overcome the difficulties produced by equally absolute titles of things and ideal goods (and thus it is to be regarded as inconsistent), it is interesting for the legal philosophers and jurists alike. It evokes not only the question of axiological basis for the intellectual property, but also of the correctness of propertarian model of copyright and patents.